SerpinE1 drives a cell-autonomous pathogenic signaling in Hutchinson–Gilford progeria syndrome - Giorgia Catarinella; Chiara Nicoletti; Andrea Bracaglia; Paola Procopio; Illari Salvatori; Marilena Taggi; Cristiana Valle; Alberto Ferri; Rita Canipari; Pier Lorenzo Puri; Lucia Latella (Cell Death and Disease, 2022)
Abstract Hutchinson–Gilford progeria syndrome (HGPS) is a rare, fatal disease caused by Lamin A mutation, leading to altered nuclear architecture, loss of peripheral heterochromatin and deregulated gene expression. HGPS patients eventually die by coronary artery disease and cardiovascular alterations. Yet, how deregulated transcriptional networks at the cellular level impact on the systemic disease phenotype is currently unclear. A genome-wide analysis of gene expression in cultures of primary HGPS fibroblasts identified SerpinE1, also known as Plasminogen Activator Inhibitor (PAI-1), as central gene that propels a cell-autonomous pathogenic signaling from the altered nuclear lamina. Indeed, siRNA-mediated downregulation and pharmacological inhibition of SerpinE1 by TM5441 could revert key pathological features of HGPS in patient-derived fibroblasts, including re-activation of cell cycle progression, reduced DNA damage signaling, decreased expression of pro-fibrotic genes and recovery of mitochondrial defects. These effects were accompanied by the correction of nuclear abnormalities. These data point to SerpinE1 as a novel potential effector and target for therapeutic interventions in HGPS pathogenesis.